The immunological synapse balances T cell receptor signaling and degradation. - Lee, K; Dinner, A; Tu, C; Campi, G; Raychaudhuri, S; Varma, R; Sims, T; Burack, W; Wu, H; Wang, J; Kanagawa, O; Markiewicz, M; et al. (2003)
The immunological synapse is a specialized cell-cell junction between T cell and antigen-presenting cell surfaces. It is characterized by a central cluster of antigen receptors, a ring of integrin family adhesion molecules, and temporal stability over hours. The role of this specific organization in signaling for T cell activation has been controversial. We use in vitro and in silico experiments to determine that the immunological synapse acts as a type of adaptive controller that both boosts T cell receptor triggering and attenuates strong signals.